Prevalence of Eosinophilic/Non Eosinophillic Nasal Polyps and Analysis of Their Presentation in Hospital Universiti Sains Malaysia Kelantan, Malaysia - Ramli, Ramiza Ramza; Mohamad, Irfan; Al-Hadeethi, Yahia Hussein (IIUM Medical Journal Malaysia, 2017)
Introduction: This study is aimed to examine the predominant inflammatory cells in nasal polyps (NP) in the local community and its correlation to the clinical presentations. Materials and Methods: The study was done retrospectively looking at patients who had undergone functional endoscopic sinus surgery (FESS) in Hospital Universiti Sains Malaysia (HUSM), Kelantan, Malaysia with a histopathological diagnosis of nasal polyposis (NP), between the years 2004 to 2008. Sixty-two patients between the ages of 18 years to 60 years old were selected and data relevant to the study were collected from the patient’s folders using a specially created form prepared for the study. The NP histopathology report from each patient underwent FESS were analysed and the patients were divided into eosinophilic and non-eosinophilic dominant group. Clinical presentations from each patient were also gathered and analysed according to the NP group. Results: In HUSM, there were a higher number of eosinophilic types NP as compared to the neutrophilic type NP which is contrary to other study conducted on Asian populations. The clinical symptom correlations between either eosinophilic or non-eosinophilic type of NP have not shown any significant associations. Conclusion: The study showed that the incidence of histological subtypes of nasal polyp in HUSM is almost the same as that found in other parts of the world (Europe and North America) which will reduce the possibility of racial or geographical influence on the pathogenesis of the nasal polyp. Clinical symptoms and presentation alone are not enough to differentiate the type of the nasal polyp without the histological study.